2022
DOI: 10.1097/iae.0000000000003608
|View full text |Cite
|
Sign up to set email alerts
|

Drainage Retinotomy Is a Risk Factor for Surgical Failure After Pars Plana Vitrectomy in Patients With Primary Uncomplicated Rhegmatogenous Retinal Detachment

Abstract: Purpose: To identify risk factors for recurrent retinal detachment after uncomplicated pars plana vitrectomy in patients with primary rhegmatogenous retinal detachment (RRD).Methods: This single-center retrospective study included patients with primary RRD who underwent 23-gauge and 25-gauge pars plana vitrectomy at Hiroshima University Hospital between January 2016 and May 2021. All patients had $3 months of follow-up. Patients were excluded if they had preoperative proliferative vitreoretinopathy worse than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This finding appears more significant considering the potential concerns related to the intraocular use of PFCL 30 and the suggested association of drainage retinotomy with surgical failure and epiretinal membrane development. 31 We recognize that our study has several limitations that are intrinsic to retrospective analysis. These include lack of standardization, incomplete data, selection bias, cases lost to follow-up, and multiple operating surgeons over a 10-year period.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This finding appears more significant considering the potential concerns related to the intraocular use of PFCL 30 and the suggested association of drainage retinotomy with surgical failure and epiretinal membrane development. 31 We recognize that our study has several limitations that are intrinsic to retrospective analysis. These include lack of standardization, incomplete data, selection bias, cases lost to follow-up, and multiple operating surgeons over a 10-year period.…”
Section: Discussionmentioning
confidence: 94%
“…This finding appears more significant considering the potential concerns related to the intraocular use of PFCL 30 and the suggested association of drainage retinotomy with surgical failure and epiretinal membrane development. 31…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established that PR is a significant risk factor for ERM formation, which is similar to the results observed in this study. 24,25 ERM formation is marked by migration and proliferation of cells to the macula, such as retinal pigment epithelium cells, glial cells, fibroblasts, and inflammatory cells. 26 It has been hypothesized that the use of a PR for drainage dislodges retinal pigment epithelial cells, releases inflammatory cells, and leads to glial cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of drainage retinectomy on the primary success rate remains a subject of debate. Ohara et al 7 recently identified drainage retinotomy as a risk factor for surgical failure after PPV in patients with uncomplicated RRD. They proposed that avoiding drainage retinotomy could enhance surgical success.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent retrospective reports have suggested that drainage retinotomy is a risk factor for the development of an ERM 7 , 20 . Previously, Ishikawa et al reported that drainage retinectomy are more likely to develop ERM after vitrectomy using J-RD registry data.…”
Section: Discussionmentioning
confidence: 99%